Going-concern Evaluation in Jordan - Al-Awaqleh, Qasim Ahmad Qasim (2008)
Jordan is still suffering from financial distress due to the continuity of its company’s failure. Jordanian laws and regulations, in addition to Inter National Standard No. 570 have considered external auditor to be responsible for the evaluation of the company’s going concern and to give an early warning to the stakeholders of any impending failure. The external auditor has to add an explanatory paragraph in his report regarding the company’s going concern. The problem in Jordan is that some of the external auditors issued unqualified opinion, and some of the companies were declared bankrupt after the issuance of the report. This issue has been confirmed by previous studies and pilot study by the researcher by investigating on 160 reports related to 32 Jordanian companies that faced such failure. Therefore, this study aimed to investigate the factors that influence the auditor’s evaluation of the company’s going concern in Jordan. The importance of this study appeared through the examination of demographic factors and auditing related factors and their relationship with the auditor evaluation of the company going concern and to provide critical recommendations to policy makers in Jordan to overcome this issue and improving the auditor report toward company’s going concern. To achieve the objectives of this study, questionnaires were administered to 473 external auditors listed with Jordanian Association of Certified Public Accountants (JACPA) for 2007. Multiple regression (Standard regression) was also used to test the study hypotheses.In general, four variables were positively significant related with the auditor evaluation of the company going concern. These variables are audit fees, social relations, hiring and dismissing the auditor, and audit firm size. On the other hand,consultant services are negatively significant related with the auditor evaluation of the company going concern. Findings of this study also showed that the demographicv and auditing-related factors significantly explained more than 51 % of the variance in the auditor evaluation of the company going concern. Jordanian government and JACPA should issue new regulations to increase the audit fees to fit the auditors work, integrate small audit firms, improve social relations, increase hiring and dismissing the auditor, and prevent consultant services given by the external auditors to their clients. On the other hand, the demographic factors were insignificant related with the auditor evaluation of the company going concern. Thus, the audit career in Jordan also needs more control, regulations, policies and systems to provide a structure for protecting the auditor's decision related to company's going concern issues. In relation to the practical and theoretical contribution, this study used new variables in new model such as audit fees, consultant services, social relations, and experience of the auditor in accounting. Furthermore, practical contribution will help policy makers and Jordanian government to advance in this area and look upon new policy toward external auditors (new laws, new auditor report) to protect the economy and the society stability.